DIGITAL CULTURE AS A COMPETITIVE ADVANTAGE IN THE SUSTAINABLE DEVELOPMENT OF ORGANIZATIONS - Vesela Serafimova; Valentin Vasilev (Agora International Journal of Economical Sciences (AIJES), 2024)
The article explores the concept of digital culture as a key component for organizations seeking sustainable development and competitive advantage in today's rapidly evolving business landscape. It delves into how embracing a digital culture within an organization can lead to enhanced efficiency, innovation, and overall performance. By fostering a culture that values digital skills, collaboration, and adaptability, companies are better equipped to navigate challenges and leverage opportunities in the digital age. There's no denying that there has been a noticeable increase in interest in recent years for solutions that support the sustainable development of organizations. In such a context, a key factor for increasing the efficiency of these processes is effective change management and its detailed knowledge. The management of human resources is affected by these management relationships, which guide it toward the strategic prioritizing of particular areas. However, given the evolving importance of technology and all of its associated aspects and activities, it is necessary to concentrate on identifying a new management paradigm, or digital culture. This is where we should also include the tendency, the primary driving force behind the changes, to be expressed in the understanding that increases in an organization's effectiveness have a direct connection to the human factor, and from there to innovative practices, talent management, motivational policies, and other aspects of personnel management. Therefore, in the search for sustainable development policies, human resources should be considered as organizational capital.
Keywords: 330